2018
DOI: 10.19082/6877
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of pretreatment intravenous fentanyl or intravenous lidocaine on suppression of fentanyl-induced cough in children: a randomized, double-blind, controlled clinical trial

Abstract: Background and aimThe injection of fentanyl usually causes coughing during induction of anesthesia. Based on a few studies about effects of lidocaine and the fact there is no study concerning the effect of fentanyl on fentanyl-induced cough in pediatric patients, the aim of this study was to compare the effectiveness of low dose of fentanyl with lidocaine in prevention of fentanyl-induced cough in children.MethodsThis randomized double-blind controlled clinical trial study was conducted at Motahari Hospital be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Several studies have demonstrated that the incidence of FIC is higher in infants and young children ( Golmohammadi et al, 2018 ; Han et al, 2010 ). Young age is one of the important factors for the occurrence of FIC.…”
Section: Influencing Factors Of Fentanyl-induced Coughmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that the incidence of FIC is higher in infants and young children ( Golmohammadi et al, 2018 ; Han et al, 2010 ). Young age is one of the important factors for the occurrence of FIC.…”
Section: Influencing Factors Of Fentanyl-induced Coughmentioning
confidence: 99%
“…According to the above-mentioned factors related to FIC, the prevention and treatment of FIC can start from the administration of the drug itself, for instance, adjusting the dose and/or concentration of fentanyl analogs, reducing the speed of administration, and selecting appropriate administration routes (such as peripheral administration, etc.). It has also been found that pre-injection of low-dose fentanyl (0.5 μg⋅kg −1 or 25 μg directly) can alleviate FIC to some extent ( Du et al, 2014 ; Golmohammadi et al, 2018 ; Hung et al, 2010 ; Shrestha et al, 2012 ). Pretreatment with a small dose of remifentanil 0.3 μg⋅kg −1 , 1 min before sufentanil injection can effectively and safely reduce the incidence of cough induced by sufentanil (4.8% vs. 31%) ( Lin et al, 2019 ).…”
Section: Prevention and Treatment Of Fentanyl-induced Coughmentioning
confidence: 99%
“…Even though there are several hypothesis and still the mechanism of FIC is unknown. Different drugs have been studied on FIC with resulted in variable reduction in incidences of FIC .While some physical factors like age 13 , ethnicity 14 and history of smoking 15 may also effect FIC. It has been studied that Asian people are more sensitive to fentanyl and its analogs.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 It is generally transitory and limited; however, it is undesirable in patients with underlying diseases, such as cerebral aneurysm, brain trauma, and hernia, dissecting aortic aneurysm, pneumothorax or reactive airway disease. 3 This is because it can not only cause rapid changes in body hemodynamics, induce cardiovascular and cerebrovascular accidents, but also increase intra-abdominal pressure and increase reflux and aspiration. 4 Although the FIC mechanism has not been fully clarified, different strategies or methods should be used to intervene, thereby reducing the occurrence or relieving this side effect.…”
Section: Introductionmentioning
confidence: 99%
“…However, FIC is often reported after intravenous fentanyl administration, and it has an incidence between 35% and 64% 1,2 . It is generally transitory and limited; however, it is undesirable in patients with underlying diseases, such as cerebral aneurysm, brain trauma, and hernia, dissecting aortic aneurysm, pneumothorax or reactive airway disease 3 . This is because it can not only cause rapid changes in body hemodynamics, induce cardiovascular and cerebrovascular accidents, but also increase intra‐abdominal pressure and increase reflux and aspiration 4 .…”
Section: Introductionmentioning
confidence: 99%